2010
DOI: 10.1186/1743-422x-7-337
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of two distinct monopartite begomoviruses infecting tomato in india

Abstract: BackgroundTomato leaf curl viruses, which are the members of the genus Begomovirus, have emerged as devastating pathogens worldwide causing huge economic losses and threatening production of crops like cassava, cotton, grain legumes and vegetables. Even though the ToLCV isolates from Northern India have been shown to possess bipartite genome (designated as DNA A and DNA B), those from Australia, Taiwan and Southern India have a single genomic component (DNA A). We describe here the genetic diversity of two iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 23 publications
1
16
0
Order By: Relevance
“…4). Pandey et al (2010) has reported similar findings in case of identification of ToLCV, a member of the genus begomovirus causing tomato leaf curl disease.…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…4). Pandey et al (2010) has reported similar findings in case of identification of ToLCV, a member of the genus begomovirus causing tomato leaf curl disease.…”
Section: Resultssupporting
confidence: 63%
“…1c). Similarly, tomato leaf curl virus (ToLCV) infection was detected in tomato plants at molecular level using ToLCV specific primers (Pandey et al 2010). One PCR amplified sample from each location was gel purified and used for automated sequencing.…”
Section: Resultsmentioning
confidence: 99%
“…However, several attempts of PCR using DNA-B-and DNA-b-specific primers failed indicating the absence of DNA-B and DNA-b molecules in infected samples; therefore, the Begomovirus was considered to be monopartite. Recently, some new monopartite Begomoviruses (Tomato leaf curl virus, Tomato yellow leaf curl virus and Papaya leaf curl China virus) have been reported from India (Pandey et al 2010), Australia (Van Brunschot et al 2010) and China (Zhang et al 2010) respectively, for which neither DNA-B nor DNA-b could be detected.…”
Section: Discussionmentioning
confidence: 99%
“…An increased symptom severity and shortened incubation period required for symptom expression was noticed when ToLCGV was coinoculated with betasatellite of tomato yellow leaf curl virus Thailand (TYLCTHB) resulted in yellow mottling [9]. The molecular relationship of ToLCGV-[Vad], an isolate from Vadodara district of Gujarat, with other strains revealed that it belongs to Old World Begomoviruses and established a closely related cluster with other North Indian strains including ToLCGV-(Varanasi)-[Var] and ToLCGV-(Mirzapur)-[Mir] based on the DNA-A sequence alignment [10]. …”
Section: Introductionmentioning
confidence: 99%